Middle-out from Bottom-up: Engineering and Close Reading Code in HBO's Silicon Valley. - Nguyen, Robert (Configurations)
This essay examines the production and reception of a selection of computer source code briefly visible onscreen in "Founder Friendly," an episode of the HBO satire series Silicon Valley. This text, made legible by the affordances of streaming high definition television, invited fans to engage in interrupted viewing, close reading, and tele-participation practices, in which they froze playback, examined, compiled, and ran the source code, and shared their interpretations and results. Yet the creation of such authentic and generative objects was enabled by a close collaboration and alignment of interests between the production team and technology industry insiders. In this case, the satire's pursuit of high-definition verisimilitude led to the replication of some of the very practices and logics it critiqued.